(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The Insurance sector plays a significant effect on the over economy by mobilizing domestic savings. Insurance turn accumulated capital into productive investments. Insurance also enables mitigation of losses, financial stability and promotes trade and commerce activities those results into sustainable economic growth and development